Evaluation of hydration of cement pastes containing high volume of mineral additions. Issue 8 (3rd August 2019) - Anjos, M. A. S.; Reis, R.; Camões, A.; Duarte, F.; Jesus, C.
Abstract: The use of mineral additions is a common practice in the production of cementitious materials. Recently proposed usage of high amounts of cement replaced by mineral additions requires the study of the chemical interaction of these additions with the cement. This study intends to evaluate, by means of TG/DTG techniques, XRD and compressive strength, the effect of high volume of mineral additions in the hydration of cementitious pastes. Pastes with 50–70% of cement replaced by mineral addition and with different combinations of fly ash and metakaolin were evaluated, two pastes without mineral addition and two other pastes with lime addition. Results showed TG/DTG and XRD techniques are more suitable for evaluating kinetics of reactions of hydration, making it possible to quantify the substantial reduction in the levels of portlandite in hydrated pastes containing high volumes of mineral additions. These techniques allowed to find important differences in the evaluation of calcium hydroxide, because its morphology can change in the presence of additions. Also showed that it is possible to achieve, enhanced or even high compressive strength (50–80 MPa) in concretes containing reduced cement contents. As well as more resistance against harmful agents and carbonation attack.